2012
DOI: 10.3892/or.2012.1706
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid sensitizes colon cancer cells to sulindac sulfide-induced apoptosis

Abstract: Abstract. Sulindac analogs represent one of the most efficacious groups of NSAIDs reducing the risk of colon cancer. Recent studies have shown that sulindac sulfide, a sulindac analog effective at lower doses compared to its parent compound, triggers the death receptor (DR)5-dependent extrinsic apoptotic pathway. Induction of apoptosis via activation of the DR-mediated pathway would be an ideal therapeutic strategy to eliminate cancer cells. In this study, we investigated the possibility that colon cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Benefits of dietary n-3 PUFA adjunct to FDA approved drugs in cancer treatment or prevention have been reported. For example, DHA combination sensitized colon cancer cells to non-steroidal anti-inflammatory drug (sulindac sulfide)-induced apoptosis, leading to enhanced growth suppression of human colon cancer xenografts (Lim et al, 2012). This noteworthy, because NSAIDs are one of the most efficacious classes of drugs used to reduce the risk of colon cancer.…”
Section: Adjunct Chemotherapeutic Potential Of N-3 Pufamentioning
confidence: 99%
“…Benefits of dietary n-3 PUFA adjunct to FDA approved drugs in cancer treatment or prevention have been reported. For example, DHA combination sensitized colon cancer cells to non-steroidal anti-inflammatory drug (sulindac sulfide)-induced apoptosis, leading to enhanced growth suppression of human colon cancer xenografts (Lim et al, 2012). This noteworthy, because NSAIDs are one of the most efficacious classes of drugs used to reduce the risk of colon cancer.…”
Section: Adjunct Chemotherapeutic Potential Of N-3 Pufamentioning
confidence: 99%
“…For example, a combination of the selective COX-2 inhibitor celecoxib and DHA led to decreased proliferation and increased apoptosis of HCA-7 human CRC cells [34]. Moreover, combined DHA and sulindac (a non-selective COX inhibitor) treatment decreased growth and increased apoptosis of three human CRC cell lines compared with either agent alone [35].…”
Section: Discussionmentioning
confidence: 99%
“…The antineoplastic activity of DHA has been indicated in many studies. DHA induces apoptosis and differentiation in human melanoma cells in vitro [26], helps prevent colorectal cancer [19], induces apoptotic cell death in human cancer cells either alone or in combination with conventional therapies, and causes selective cytotoxicity towards cancer cells with little or no toxicity on normal cells [27]. DHA can induce apoptosis in tumor cells in vitro and in vivo, in a dose- and time-dependent manner in tumor cell lines derived from a wide range of solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that docosahexaenoic acid exhibits a time- and concentration-dependent antiproliferative effect on various human cancer cell lines while having minimal cytotoxicity on the normal or non-tumorigenic cells [5,17], cause cell cycle arrest, or even apoptosis and presents synergistic anticancer properties with other drug substances [1,18,19]. Enormous data from cancer cell lines and in vivo cancer models have given insight into the mechanisms underlying the anticancer effects of ω-3 PUFAs [20,21].…”
Section: Introductionmentioning
confidence: 99%